Method to prepare aqueous propolis dispersions based on phase separation. (30th September 2022) - Monteil, Julien; Hadj-Sassi, Abdessattar; Dargelos, Élise; Guzman-Barrera, Nydia; Poque, Emmanuelle; Leal-Calderon, Fernando
Abstract: Propolis has many benefits for human health. To facilitate its oral consumption, we designed propolis-in-water dispersions to be used as nutraceuticals. Propolis was first dissolved either in ethanol or in a hydroalcoholic solution. Water being a non-solvent for propolis, its addition produced propolis precipitation. We explored the ternary phase diagram of water, propolis and ethanol to identify the line separating the one phase region where propolis is fully dissolved, and the two-phase region where a concentrated propolis solution coexists with a dilute one. Droplets rich in propolis were produced during the phase separation process under mechanical stirring induced by a rotor–stator device or a microfluidizer, and they were stabilized using gum Arabic as an emulsifier. Ethanol was finally removed by distillation under reduced pressure. Propolis dispersions in the micron and submicron size range could be obtained. They contained between 1.75 and 10.5 wt% polyphenols relative to the total mass.